1993
DOI: 10.1016/0014-5793(93)81684-r
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a vasoactive peptide related to lysyl‐bradykinin from trout plasma

Abstract: Incubation of plasma from the steelhead trout, Oneorhynehus mykiss with porcine pancreatic glandular kallikrein generated bradykinin-like immunoreactivity. The primary structure of the immunoreactive peptide was established as: Lys-Arg-Pro-Pro-Gly-Trp-Ser-Pro-Leu-Arg. This sequence shows two amino acid substitutions (Phe6--~Trp and Phe9--*Leu) compared with mammalian lysyl-bradykinin (kallidin). Bolus intraarterial injection of the purified peptide produced a strong and sustained vasopressor response in the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It is not clear, for example, what protease cleaves kinins from kininogen in fish, given that a typical prekallikrein gene is absent. It is well established that bradykinin occurs in fish plasma and is released from a precursor kininogen by exogenous kallikreins isolated from mammalian pancreas [17] . It has also been reported that a pair of tandemly arranged bradykinin receptors are present in bony fish in the same way they are in birds and mammals [18] .…”
Section: Parallel Evolution Of Kininogens and Contact Factor Proteasesmentioning
confidence: 99%
“…It is not clear, for example, what protease cleaves kinins from kininogen in fish, given that a typical prekallikrein gene is absent. It is well established that bradykinin occurs in fish plasma and is released from a precursor kininogen by exogenous kallikreins isolated from mammalian pancreas [17] . It has also been reported that a pair of tandemly arranged bradykinin receptors are present in bony fish in the same way they are in birds and mammals [18] .…”
Section: Parallel Evolution Of Kininogens and Contact Factor Proteasesmentioning
confidence: 99%
“…Both cod and wolffish kininogens carried the fish bradykinin peptide RPPGWSPLR that we have previously shown to be present in Atlantic salmon kininogen [6]. The fish bradykinin peptide has also been found previously from enzyme‐treated plasma of Atlantic cod [5] and steelhead trout [4]. Most of the determined peptide sequences could be aligned with the heavy chain of human kininogen (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…Kininogens have been characterized from many mammals including human, bovine, rat [1], and recently whale [3]. In addition, there are reports on bradykinins in fish including steelhead trout [4] and Atlantic cod [5]. We have recently isolated a kininogen and another high molecular mass cysteine proteinase inhibitor from the skin of Atlantic salmon [6].…”
mentioning
confidence: 99%
“…Studies by Lipke and co-workers 11,12 demonstrated that treatment of plasma from the rainbow trout, Oncorhynchus mykiss, with porcine pancreatic kallikrein generated vasoactive peptide(s), termed T60K . Following this work, 13 we obtained a strong indication of the existence of a kallikrein-kinin system in nontetrapods by demonstrating that incubation of heat-denatured trout plasma with porcine kallikrein generated [Lys 0 , Trp 5 , Leu 8 ]-BK. More recently, 14 we have isolated in much higher yield a second BK-related peptide from kallikrein-treated trout plasma whose primary structure was established as [Arg 0 , Trp 5 , Leu 8 ]-BK (FIG.…”
Section: Teleost Fishmentioning
confidence: 82%